Genome‐wide transcriptomic and proteomic analyses of bollworm‐infested developing cotton bolls revealed the genes and pathways involved in the insect pest defence mechanism. Issue 6 (22nd January 2016) - Kumar, Saravanan; Kanakachari, Mogilicherla; Gurusamy, Dhandapani; Kumar, Krishan; Narayanasamy, Prabhakaran; Kethireddy Venkata, Padmalatha; Solanke, Amolkumar; Gamanagatti, Savita; Hiremath, Vamadevaiah; Katageri, Ishwarappa S.; Leelavathi, Sadhu; Kumar, Polumetla Ananda; et al.
Summary: Cotton bollworm, Helicoverpa armigera, is a major insect pest that feeds on cotton bolls causing extensive damage leading to crop and productivity loss. In spite of such a major impact, cotton plant response to bollworm infection is yet to be witnessed. In this context, we have studied the genome‐wide response of cotton bolls infested with bollworm using transcriptomic and proteomic approaches. Further, we have validated this data using semi‐quantitative real‐time PCR. Comparative analyses have revealed that 39% of the transcriptome and 35% of the proteome were differentially regulated during bollworm infestation. Around 36% of significantly regulated transcripts and 45% of differentially expressed proteins were found to be involved in signalling followed by redox regulation. Further analysis showed that defence‐related stress hormones and their lipid precursors, transcription factors, signalling molecules, etc. were stimulated, whereas the growth‐related counterparts were suppressed during bollworm infestation. Around 26% of the significantly up‐regulated proteins were defence molecules, while >50% of the significantly down‐regulated were related to photosynthesis and growth. Interestingly, the biosynthesis genes for synergistically regulated jasmonate, ethylene and suppressors of the antagonistic factor salicylate were found to be up‐regulated, suggesting a choice among stress‐responsive phytohormone regulation. Manual curation of the enzymes and TFs highlighted the components of retrograde signalling pathways. Our data suggest that a selective regulatory mechanism directs the reallocation of metabolic resources favouring defence over growth under bollworm infestation and these insights could be exploited to develop bollworm‐resistant cotton varieties.